Quantitative feature analysis of continuous analytic wavelet transforms of electrocardiography and electromyography. (9th July 2018) - Wachowiak, Mark P.; Wachowiak-Smolíková, Renata; Johnson, Michel J.; Hay, Dean C.; Power, Kevin E.; Williams-Bell, F. Michael
Abstract : Theoretical and practical advances in time–frequency analysis, in general, and the continuous wavelet transform (CWT), in particular, have increased over the last two decades. Although the Morlet wavelet has been the default choice for wavelet analysis, a new family of analytic wavelets, known as generalized Morse wavelets, which subsume several other analytic wavelet families, have been increasingly employed due to their time and frequency localization benefits and their utility in isolating and extracting quantifiable features in the time–frequency domain. The current paper describes two practical applications of analysing the features obtained from the generalized Morse CWT: (i) electromyography, for isolating important features in muscle bursts during skating, and (ii) electrocardiography, for assessing heart rate variability, which is represented as the ridge of the main transform frequency band. These features are subsequently quantified to facilitate exploration of the underlying physiological processes from which the signals were generated. This article is part of the theme issue 'Redundancy rules: the continuous wavelet transform comes of age'.